PENGETAHUAN SEBAGAI FAKTOR PENENTU PERILAKU SAFETY DRIVING PADA PENGEMUDI TRUK - aini, nur; Indrawati, Ririn; Rusmiati, Desi (STIKes Medistra Indonesia, 2021)
Traffic accidents are one of the factors causing the high morbidity and mortality rates. This is an attribute to the unsafe behavior of the vehicle driver. The purpose of this research is to decide the unsafe behavior factors for truck drivers of a company. Quantitative research methods with logistic regression design using primary data. Sampling with simple random sampling was obtained as many as 95 respondents. The results showed that the variables that influenced unsafe behavior where knowledge (p = 0.014), education (0.001), and vehicle conditions (p = 0.049). Work experience (p = 0.190) Age (p = 0.865) with confounding variables where education and vehicle condition. Drivers behave unsafely such as driving high-speed on slippery roads because they do not know the safe limits for driving speed and distance. Conclusion. The most influential factor is knowledge, therefore the company needs to offer periodic training and evaluation of knowledge, health, and driver knowledge